Student Perceptions of The Teslameter Tool Using Arduino Nano With a Hall Effect Sensor for Magnetic Field Material As a Support in Physics Learning - Novyantry Andika; DIan Pertiwi Rasmi; Menza Hendri (Science and Mathematics Education Journal, 2025)
The purpose of this study was to analyze student perceptions of teslameter tools using arduinonano with hall effect sensors for magnetic field material as support in physics learning. This research method uses a descriptive qualitative approach. The subjects of this research are students majoring in science / who take physics lessons at SMAN 1 Jambi City. The instrument used in this study was an interview with 8 questions. The results of research on student perceptions of teslameter tools using arduinonano with hall effect sensors for magnetic field material as support in physics learning, show that the use of teslameter tools really helps students in understanding magnetic field material in physics learning directly, so that it can increase student interest in learning physics and make learning more effective and can improve student learning outcomes. It can be concluded that teachers have an important role in learning, so teachers should more often use practicum tools, especially teslameter as a tool in the physics learning process of magnetic field material. It is expected that teslameter tools are sufficiently available in school physics laboratories and more practicum or experiments that use teslameter tools to help students better understand magnetic field material.